BUILDING A SUSTAINABLE BUSINESS ECOSYSTEM IN VILLAGES: THE ROLE OF FINANCIAL LITERACY AND ACCOUNTABILITY IN ENCOURAGING STUDENT INTENTIONS - Dananjaya, I Gusti Ngurah Agung; Prayudi, Made Aristia; Paradila, I Made Pradnyana; Wikantara, I Wayan Adi (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
In the era of rapid digital transformation, technology-based financial management has become a crucial aspect in the development of Micro, Small, and Medium Enterprises (MSMEs), especially in tourist villages that rely on innovation and digital competitiveness. However, along with the development of digital technology, many MSME actors in tourist villages face challenges in managing finances effectively. Limitations in financial literacy and understanding of accountability are major obstacles in adapting to the digital financial system. The main objective of this study is to analyze the influence of financial literacy and perceptions of accountability on students' intentions in managing digital-based MSME finances in tourist villages. The novelty of this study lies in the relationship between financial literacy and perceptions of accountability in relation to digital-based MSME financial management in tourist villages which has not been widely studied. The primary data for this study was obtained through questionnaires that were distributed directly to the selected respondents. Based on the calculation of the Slovin formula, 91 samples were obtained. Data analysis used SPSS version 25 to test the relationship between variables, including: reliability tests, validity tests, and multiple linear regression analysis. The findings in this study conclude that financial literacy and perception of accountability and the relationship between the two have a positive and significant influence on students' intentions in managing digital-based MSME finances in tourist villages. This study is expected to contribute to the development of strategies to improve financial literacy and accountability among students, so that they can play an active role in supporting digital-based MSME financial management in tourist villages. In addition, this study provides a real contribution in encouraging collaboration between the younger generation and MSME actors through strengthening the capacity of literacy and responsible digital financial governance, which ultimately supports the sustainability of the tourist village economy in a sustainable manner.